Profil Klinikopatologik Metastasis Kelenjar Getah Bening pada Karsinoma Ovarium di Departemen Patologi Anatomik FKUI/RSCM 2016-2018 - Hayati, Amal; Tjahjadi, Hartono (Majalah Patologi Indonesia, 2023)
Background Ovarian cancer is one of the most common malignancies in women. In Indonesia, this incidence is the third highest after breast and cervical cancer. The prognosis for ovarian carcinoma is generally poor. Ovarian cancer patients have low survival rate since most of them diagnosed at advanced stage. The tumor spread to retroperitoneum lymph nodes is important to evaluate considering that metastasis to lymph nodes will upstage the tumor to stage III. Tumor histological type, grade and CA 125 serum level considered as risk factors for lymph node metastases. Methods This study was a cross-sectional descriptive study to determine the profile of lymph node metastases in ovarian carcinoma at the Anatomical Pathology Department FKUI-RSCM for 3 years. The assessment criteria included demographic, clinical, and histopathological features of tumor mass and retroperitoneum lymph nodes. Results Analysis of demographic data in 54 cases of ovarian carcinoma found 47 patients (87%) aged ≥40 years. Unilateral tumors found in 42 cases (77.8%) and bilateral tumors found in 12 cases (22.2%). Patients generally diagnosed at stage III as many as 17 cases (31.4%). Elevated levels of tumor marker CA 125 (≥35 u/ml) found in 41 cases (76%). A total of 19 cases of ovarian carcinoma had spread to lymph nodes, with 8 cases (42%) of which were serous carcinomas. Lymph node metastases found in 16 cases (80%) of high-grade ovarian carcinoma and 12 cases (60%) of advance-staged tumors. Macrometastatic tumor deposit patterns found in 180 lymph nodes and micrometastases found in 10 lymph nodes. Two subjects diagnosed for lymph node metastases only from micrometastasis deposit in lymph nodes. Conclusion Lymph node metastases in ovarian carcinoma are more frequently found in serous carcinoma, high grade carcinoma, and cases with elevated CA125 serum level. Lymph nodes evaluation should be conducted carefully to detect micrometastasis deposit.